Establishment of Learners’ Character Through Learning Traditional Dance in Senior High School - Riyaningsih, Etik; Maryono, Maryono; Harini, Harini (Harmonia: Journal of Arts Research and Education, 2018)
This research was conducted to describe the character establishment of learners through learning dance in terms of the learning process, exercises and elements of traditional dance. This research was conducted to find and explain the process of learning traditional dance in the development of learners’ character establishment. This research data is in the form of information, documents and learning process collected through interview, literature study and observation. Meanwhile, triangulation method is done to test the validity of data from those various sources. The result shows that learning the traditional dance of Bajul Mahambara can enrich the experience of learners and on the other hand train the intellect and sense by understanding the characters of local wisdom contained in traditional dance. Learning traditional dance can give a positive influence in establishing the character of learners which are (1) religiosity; (2) honesty; (3) responsibility and cooperation; (4) tolerance; (5) discipline; (6) creativity.